(untitled) (Global Journal of Human-Social Science, 2017)
African literary discourse has shown its inherent aesthetics by giving meaning to its contents. This aesthetics revolves around the experiences of Africans as a people, which include among others, their environment, culture, socio-political and economic marginalization. Dreams from the Creeks is aesthetically structured to resonate the many unheard voices of the downtrodden people of the Niger Delta who have been suffering from political and economic deprivation over the decades, coupled with the environmental degradation resulting from oil exploration and exploitation. The language is expressed to effectively portray the lifestyle of the people thus adding beauty to an emotive discourse as a way of giving an explicit meaning to the contents as a way of soothing the psychological pain inflicted on their psyche. As a Romantic poetry, it expresses the nostalgia of human being as a result of man’s dislocation from Nature, or better still, mother Earth.